Covert dose reduction is a distinct type of medication non-adherence observed across all care settings in Inflammatory Bowel Disease. (1st December 2014) - Mountifield, Réme; Andrews, Jane M.; Mikocka-Walus, Antonina; Bampton, Peter
Abstract: Background: Non-adherence by dose omission is common and deleterious to outcomes in Inflammatory Bowel Disease (IBD), but covert dose reduction (CDR) remains unexplored. Aims: To determine frequency and attitudinal predictors of overall medication non-adherence and of covert dose reduction as separate entities. Methods: A cross sectional questionnaire was undertaken involving IBD patients in three different geographical regions and care settings. Demographics, medication adherence by dose omission, and rate of patient initiated dose reduction of conventional meds without practitioner knowledge (CDR) were assessed, along with attitudes toward IBD medication. Results: Of 473 respondents (mean age 50.3 years, 60.2% female) frequency of non-adherence was 21.9%, and CDR 26.9% (p < 0.001). By logistic regression, significant independent predictors of non-adherence were dissatisfaction with the patient–doctor relationship (p < 0.001), depression (p = 0.001), anxiety (p = 0.047), and negative views regarding medication efficacy (p < 0.001) or safety (p = 0.017). Independent predictors of covert dose reduction included regular complementary medicine (CAM) use (p < 0.001), experiencing more informative (p < 0.001) and comfortable (p = 0.006) consultations with alternative practitioners, disbelieving doctor delivered information (p = 0.021) and safety concerns regarding conventional medication (p < 0.001). Neither the frequency of non-adherence (p = 0.569) nor CDR (p = 0.914) differed between cohorts by different treatment settings. Conclusions: Covert dose reduction of IBD medication is more common than omission of medication doses, predicted by different factors to usual non-adherence, and has not been previously reported in IBD. The strongest predictor of CDR is regular CAM use.